2018
DOI: 10.3390/ijms19082426
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Schistosoma japonicum Acetylcholinesterase Affects Parasite Growth and Development

Abstract: To further investigate the importance of Schistosoma japonicum acetylcholinesterase (SjAChE) in cholinergic signaling for parasite growth and development, we used RNA interference (RNAi) to knock-down its expression in adults and eggs in vitro. This resulted in its reduced transcription but also expression of other important genes involved both in cholinergic signaling and glucose uptake were impacted substantially. Significant decreases in AChE protein expression, AChE enzymatic activity, and glucose uptake w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 54 publications
3
26
0
Order By: Relevance
“…A recent study by us [ 8 ] documented the existence of three Sm ChE paralogs (two acetylcholinesterases— smache1 and smache2 —and one butyrylcholinesterase (BChE)— smbche1 ), and we showed that each molecule localized to the tegument of adults and schistosomula and demonstrated, through RNAi-mediated suppression in vitro and in vivo , that each paralog was essential to parasite survival. We also reported a significant reduction in the glucose-scavenging ability of silenced parasites, providing evidence for the involvement of tegumental AChE in the mediation of exogenous glucose uptake, which has also been documented by other studies [ 12 , 13 , 14 ]. Despite the fundamental roles that SmChEs appear to play in parasitism, it remains to be determined which Sm ChE paralogs are effective vaccine targets in Schistosoma mansoni .…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…A recent study by us [ 8 ] documented the existence of three Sm ChE paralogs (two acetylcholinesterases— smache1 and smache2 —and one butyrylcholinesterase (BChE)— smbche1 ), and we showed that each molecule localized to the tegument of adults and schistosomula and demonstrated, through RNAi-mediated suppression in vitro and in vivo , that each paralog was essential to parasite survival. We also reported a significant reduction in the glucose-scavenging ability of silenced parasites, providing evidence for the involvement of tegumental AChE in the mediation of exogenous glucose uptake, which has also been documented by other studies [ 12 , 13 , 14 ]. Despite the fundamental roles that SmChEs appear to play in parasitism, it remains to be determined which Sm ChE paralogs are effective vaccine targets in Schistosoma mansoni .…”
Section: Introductionsupporting
confidence: 88%
“…Glucose uptake in adult worms was also significantly reduced by anti- Sm ChE antibody treatment. The cholinergic action of surface AChE has been implicated in mediation of the glucose scavenging mechanism in schistosomes [ 12 ], AChE-inhibitory metal complexes reduce glucose import in the parasites [ 13 ], and we and others have shown that RNAi-mediated silencing of schistosome che genes lessens the uptake of glucose by these parasites [ 8 , 14 ], so it is possible that antibody-mediated impairment of AChE involvement in the glucose uptake pathway is the cause of this effect. It may be that there is some redundancy in the cholinergic functioning of these molecules (even BChEs, like Sm BChE1, can perform a cholinergic role in situations of AChE deficiency [ 32 ]), so collective inhibition of the molecules is required to produce a functional deficit.…”
Section: Discussionmentioning
confidence: 99%
“…Silencing of the TsASP2 gene also impeded other T. spiralis developmental stages, as adult worms recovered from mice infected with siRNA-treated larvae were shorter than those recovered from the control and PBS groups. Specific gene silencing by RNAi has been widely applied for gene function identification in other parasites [62,63], and the results of the present study indicated that TsASP2 played a crucial role in T. spiralis invasion of IEC, and silencing of the TsASP2 gene significantly reduced larval infectivity and development in mice.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 51%
“…In schistosomes, AChE has been localized to the tegument as well as the neuromusculature [16,20,21] and a proposed function for tegumental AChE has been mediation of glucose uptake by the parasite from the external environment [22]. The exact mechanism for this process is still unclear but the proposed initiating step is by limiting the interaction of host ACh with tegumental nicotinic ACh receptors (nAChRs), a hypothesis bolstered by the observation that glucose uptake is ablated by the use of membraneimpermeable AChE and nAChR inhibitors in S. mansoni [22,23] and RNAi-mediated AChE silencing in S. japonicum [24]. The nAChRs are also associated both spatially and temporally with surface AChE expression and are concentrated on the tegument [25], the major site of glucose uptake [26].…”
Section: Introductionmentioning
confidence: 99%